Assessment of Alveolar Bone and Periodontal Status in Peritoneal Dialysis Patients - Sun, Kristine; Shen, Hui; Liu, Yingli; Deng, Hai; Chen, Huiwen; Song, Zhongchen (Frontiers in Physiology, 2021)
Chronic kidney disease (CKD) affects 8–13% of the global population and has become one of the largest burdens on healthcare systems around the world. Peritoneal dialysis is one of the ultimate treatments for patients with severe CKD. Recently, increasing severe periodontal problems have been found in CKD patients. Periodontitis has been identified as a new variable risk factor for CKD. The aim of this study was to investigate the periodontal status and severity of alveolar bone loss in CKD patients with peritoneal dialysis (PD). One hundred and six patients undergoing PD (experimental group) and 97 systemically healthy periodontitis patients (control group) were enrolled. The differences in the dimensions of the alveolar bone between two groups were compared, and the distribution of alveolar bone defects were analyzed by cone-beam computed tomography (CBCT). Gingival index (GI), plaque index (PLI), periodontal probing depth (PPD), and attachment loss (AL) were recorded. The levels of inflammatory factors in gingival crevicular fluid were assessed by ELISA. Compared to control group, there was a higher degree of alveolar bone loss in maxillary premolars, maxillary 2nd molar and mandibular 1st molar in patients with peritoneal dialysis(p<0.05). A comparison of bone loss in different sites revealed that the area with the highest degree of bone loss was on the mesial-buccal, mid-buccal, distal-buccal, and mesial-lingual site in PD patients. The expression levels of inflammatory factors were higher in experimental group (p<0.01). In conclusion, PD patients presented more severe periodontal and inflammatory status than systemically healthy periodontitis patients. The loss of the alveolar bone differed between the two groups. Different sites and teeth exhibited a diverse degree of bone loss.This study highlights that clinicians should pay close attention to periodontal status of peritoneal dialysis patients and provides a new thinking to improve healthcare for CKD.